Cornstarch-based biopolymer electrolyte doped with Na3PO4 / Syakirah Shahrudin and Azizah Hanom Ahmad - Shahrudin, Syakirah; Ahmad, Azizah Hanom (2016)
-In this work, polymer electrolytes have been prepared by doping starch with Sodium Phosphate (Na3PO4). The incorporation of 25% Na3PO4 optimizes the room temperature conductivity of the electrolyte at 7.27 x 10-6 Scm-1. The temperature dependence of conductivity for the electrolyte is Arrhenius and the activation energy, Ea, of 75% corn starch-25% Na3PO4 electrolyte is 0.26eV. The dielectric studies reveal the non-Debye nature of the electrolyte. The complexation of Na3PO4 with the polymer host was studied using Fourier transform infrared (FTIR) spectroscopy.